Teaching management to reading and writing in children of elementary school: a diagnosis - Mariela González-López (International Journal of Educational Administration, Management, and Leadership, 2021)
It is a study that seeks to make a diagnosis to locate the teaching-learning of first grade students, through the analysis and management of anthropological files, teaching models for the development of reading and writing of first grade children from elementary school. Under the qualitative analytical and methodological methodology. With the aim of promoting a procedural methodology and file management for the design and application of a diagnosis for the teaching of literacy in elementary school, such as the development of basic communication skills, knowledge of the environment, teaching of reading, writing and math. The results are that management is obtained from the anthropological files of children in elemental school, preparation of diagnoses for each student body, n addition to the stage of development, didactic strategies based on the expected learning of the study programs and to take successfully accomplished literacy. It is concluded that the management of files for the development of ready and writing essential to strengthen teaching practice and success in teaching.